2014
DOI: 10.1186/1752-1947-8-166
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of aneurysmal subarachnoid hemorrhage and surgically identified pituitary apoplexy: a case report and review of the literature

Abstract: IntroductionA ruptured aneurysm associated with a pituitary apoplexy is rare. We present the first case report of the coexistence of a ruptured posterior communicating aneurysm with a surgically discovered pituitary apoplexy where the pituitary apoplexy had not been diagnosed by a pre-operative computerized tomography scan.Case presentationA 31-year-old right-handed Chinese woman began to experience severe headache, vomiting and blurred vision which continued for two days. On admission to the hospital, a brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The rare association between a ruptured aneurysm with SAH and pituitary apoplexy [83] as well as the rupture of an aneurysm embedded within a pituitary adenoma with a clinical evidence of epistaxis has also been reported [84]. Suzuki et al reported a case of pituitary apoplexy caused by an unsuspected aneurysm bleeding into a pituitary adenoma and in which catastrophic intraoperative haemorrhage occurred [85].…”
Section: Radiological Findingsmentioning
confidence: 99%
“…The rare association between a ruptured aneurysm with SAH and pituitary apoplexy [83] as well as the rupture of an aneurysm embedded within a pituitary adenoma with a clinical evidence of epistaxis has also been reported [84]. Suzuki et al reported a case of pituitary apoplexy caused by an unsuspected aneurysm bleeding into a pituitary adenoma and in which catastrophic intraoperative haemorrhage occurred [85].…”
Section: Radiological Findingsmentioning
confidence: 99%
“…Although our case reveals pituitary apoplexy as the cause of xanthochromia, others have reported the association of apoplexy in conjunction with SAH [3][4][5][6]. Interestingly, there is some association between intracranial aneurysms and pituitary adenomas [7].…”
Section: Discussionmentioning
confidence: 64%
“…In all three cases, postoperative imaging documented a small posterior circulation aneurysm (top basilar, basilar artery-superior cerebellar artery segment, and P1 segment). Preoperative workup never disclosed clearly the presence of the aneurysm, and in contrast with reported cases regarding intraoperative rupture of anterior circulation aneurysms, all three patients had a fatal outcome [5,6,15,16]. Hemodynamic changes are less likely to occur in the posterior circulation while removing a pituitary adenoma or a craniopharyngioma compared with the anterior circulation.…”
Section: Discussionmentioning
confidence: 71%